Qualitative Analysis of Pattern of Finger Print in Relation to Gender and Blood Group (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Identification of a person means the determination of the individuality or recognition of that person. A fingerprint system also known as dactylography, is based on the principle that the skin of the balls of the fingers and thumb is covered with characteristics ridges and grooves, the pattern of which makes absolute identification possible. These pattern have major design which enables them to be placed in group for primary classification, and a considerable amount of final detail – of branching and coalescence of ridges, of island, core and delta arrangement permitting subgrouping, and an unlimited quantity of extremely fine pore details along individual ridges. In this study an attempt has been made to analyze their correlation with blood group and gender of individuals. This prospective study was carried out over a period of 6 months (May 2019-October 2019) among 100 medical students (50 male and 50 female) belonging to the age group of 21 -25 years of GSVM Medical College, Kanpur (U.P.) India, Results show that each fingerprint is unique; loops are the most commonly occurring finger print pattern while arches are the least common. Males have a higher incidence of whorls and females have a higher incidence of loops. Loops are predominant in blood group A while whorls are more common in blood group B individuals.
Keywords: Types of fingerprints; Blood group; Gender